Prevalence of Anterior Inferior Iliac Spine Dysmorphism and Development of a Novel Classification System: An Anatomic Study of 1,797 Cadaveric Specimens - Knapik, Derrick M.; Fortun, Chad M.; Schilf, Christopher R. J.; Nho, Shane J.; Salata, Michael J. (Frontiers in Surgery, 2021)
Purpose: Subspine impingement occurs due to a morphologically abnormal anterior inferior iliac spine (AIIS), capable of causing impingement against the distal femoral neck. The purpose of this investigation was to determine the prevalence of AIIS dysmorphism based on specimen sex, race and age, while introducing a novel anatomic-based classification system. Methods: A total of 1,797 adult cadaveric specimens (n=3,594 hemipelvises) were analyzed. AIIS with the potential for subspine impingement (SSI) was recorded in each specimen by two independent authors. Specimens with AIIS dysmorphism were then reexamined to determine SSI subtype using a novel descriptive anatomic classification system. Results: AIIS dysmorphism was present in 6.4% (n=115 of 1797 specimens) of specimens and 5.2% (n=186 of 3,594) of hemipelvises. Dysmorphism was significantly more common in male specimens (p=0.04) and African-American specimens (p=0.04). No significant overall difference in prevalence was appreciated based on specimen age (p=0.89). Subtype classification found that 67% of hemipelvises possessed a columnar type AIIS, 30% were bulbous and 3% hook type. Males possessed a significantly higher prevalence of columnar type AIIS dysmorphism (p<0.001). No significant overall differences in anatomic classification were appreciated based on race (p=0.12) or when analyzed based on age (p=0.34). Conclusion: AIIS dysmorphism was present in 6.4% of the 1,797 cadaveric specimens evaluated. African-American and male specimens possessed significantly higher prevalence of AIIS dysmorphism, with no significant difference based on specimen age. Columnar type AIIS dysmorphism was most common. Anatomic classification was not significantly different based on specimen race or age. Level of Evidence: Case Series, Level IV Key Words: Subspine; Impingement; Hip; Cadaver; Anatomy